M1 Computed tomography prior to transcatheter aortic valve implantation in the United Kingdom. (7th September 2020) - Harries, Iwan; Weir-McCall, Jonathan R; Williams, Michelle C; Shambrook, James; Roditi, Giles; Bull, Russell; Morgan-Hughes, Gareth J; Nicol, Edward D; Moss, Alastair J
Abstract : Introduction: This cross-sectional study sought to survey the current practice of computed tomography prior to transcatheter aortic valve implantation (CT-TAVI) in the United Kingdom. Methods: All members of the British Society of Cardiovascular Imaging (BSCI) were invited to complete a 27-item online CT-TAVI survey. Results: 47 responses were received from 40 cardiac centres, 23 (58%) of which performed TAVI on-site (TAVI centres). Only 6 respondents (13%) performed high volume activity (>200 scans per year) compared with 13 (28%) performing moderate (100–200 scans per year) and 27 (59%) performing low (0–99 scans per year) volume activity. Acquisition protocols varied (41% retrospective, 12% prospective with wide padding, 47% prospective with narrow padding), as did the phase of reporting (45% systolic, 37% diastolic, 11% both, 6% unreported) and use of beta blockade (22%). Median dose length product (DLP) was 675 mGy.cm (interquartile range 477 - 954 mGy.cm). Compared with non-TAVI centres, TAVI centres were more likely to report minimum ilio-femoral luminal diameter (n=25, 96% versus n=7, 58%, p=0.003) and optimal tube angulation for intervention (n=12, 46% versus n=1, 8%, p=0.02). TAVI centres trended towards using lower contrast volume than non-TAVI centres (98±27 vs. 118±42 ml, p=0.06); radiation doses did not differ (766±502 vs 801±461mGy.cm, p=0.66). Conclusion: This national survey formally describes current CT-TAVI practice in the United Kingdom. High volume activity was only present at 1 in 7 cardiac CT centres. There is wide variation in scan acquisition, scan reporting and radiation dose exposure.